Knowledge, perceptions and attitudes on the sexuality of nursing students and teachers - Dias, Helia (2016)
Introduction: The personal attitudes regarding specific aspects of sexuality are of interest to practices of personal concern, as they are to practices inserted in professional roles. General attitudes towards sexuality and sexual health were evaluated. Objectives: To describe the perceptions and attitudes of students and nursing teachers about sexuality. Methods: We used a mixed methods design with a sequential strategy: QUAN→qual of descriptive and explanatory type. 646 students and teachers participated. The Sexual Attitudes Scale (EAS) of Hendrick & Hendrick (Alferes, 1999) and Attitude Scale Address Sexual and Reproductive Health (EAFSSR) of Nemčić et al (Abreu, 2008) were used. Results: There are significant differences in the level of knowledge about sexuality depending on the sample (χ2KW (2)=18.271; p=.000): students of 1st year have lower levels. The profile of the four dimensions of EAS per sample is identical in all 3 samples, having responsibility the highest average value. In subscales EAFSSR per sample and sex there are significant diferences (p<.05) for all samples and uniform pattern was noted: females have higher median values, indicating that they have more favorable attitudes towards sexual health. Conclusions: Sexual attitudes reveal a multidimensional structure based in the female identity, that shows responsibility towards family planning and sexual education, as well as towards individual self-care regarding the body and sexual and reproductive health. An attitudinal profile by gender emerges, accentuating the polarity between male and female. The importance of the training process in nursing following the personal and social development of students is corroborated.